2022
DOI: 10.3390/children9101448
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 History Increases the Anxiety of Mothers with Children in Intensive Care during the Pandemic in Turkey

Abstract: This study aimed to examine the mental status of mothers whose children were hospitalized during the COVID-19 pandemic, especially in places where risk factors are higher such as pediatric intensive care units, and to contribute to the development of psychological health policies, especially for these high-risk groups in epidemic situations. Method: This descriptive cross-sectional study was conducted between January 2021 and July 2021. The population of the study was mothers whose children were hospitalized i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
0
2
1
Order By: Relevance
“…Conversely, Yildiz et al ( 2022) examined the impact of the COVID-19 pandemic on the anxiety of mothers with children requiring special care in Turkey. They observed that maternal anxiety increased with the age of the children, contradicting our results [37]. The discrepancy between this study and ours could potentially stem from variations in the health status of the children under study (requiring intensive care) and the assessment tool utilized to measure COVID-related anxiety.…”
Section: Discussioncontrasting
confidence: 99%
“…Conversely, Yildiz et al ( 2022) examined the impact of the COVID-19 pandemic on the anxiety of mothers with children requiring special care in Turkey. They observed that maternal anxiety increased with the age of the children, contradicting our results [37]. The discrepancy between this study and ours could potentially stem from variations in the health status of the children under study (requiring intensive care) and the assessment tool utilized to measure COVID-related anxiety.…”
Section: Discussioncontrasting
confidence: 99%
“…These groups may be at increased risk of developing depression and other mental health problems because of the added stress and challenges they have faced. Other interesting topics to discuss in future work are the mental health of people whose sexual lives as couples were altered during the pandemic [ 29 ], as well as the mental health of parents whose children were hospitalized due to COVID-19 [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Familycentered rounds include discussion with family members present, although there is variability in the specific aspects of implementation [11]. Due to the importance of parents being present in the NICU, their mental and physical health during this challenging time has been increasingly explored [12,13]. Despite the establishment of parent involvement as best practice, the technical, fast-paced, and demanding environment of the NICU can be inconsistent in supporting the establishment of parent-provider working relationships [13,14].…”
Section: Introductionmentioning
confidence: 99%